2016
DOI: 10.1039/c6cp05804c
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the effect of CO2absorption on the ionic mobility of ionic liquids

Abstract: We investigate a comparative effect of CO absorption on the ionic mobility of two choline based ionic liquids comprising two different anions such as threonine and imidazole. The synthesized ionic liquids were characterized using H andC NMR and other spectroscopic techniques. By keeping a common cation and changing the anion from threonine to imidazole both the viscosity and density reduced drastically. We found that [N][Imi] exhibits the highest CO capture capacity at 20 °C of 5.27 mol of CO per kg of ionic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 41 publications
1
48
0
Order By: Relevance
“…Temperature dependences of D for ILs often follow the Vogel–Fulcher–Tamman (VFT) equation for diffusivity, which is described by the following equation: D=D0exp()B()TT0 where D 0 , T 0 , B are adjustable parameters. Energy of activation for diffusion is related with B as E D = B ⋅ R .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature dependences of D for ILs often follow the Vogel–Fulcher–Tamman (VFT) equation for diffusivity, which is described by the following equation: D=D0exp()B()TT0 where D 0 , T 0 , B are adjustable parameters. Energy of activation for diffusion is related with B as E D = B ⋅ R .…”
Section: Resultsmentioning
confidence: 99%
“…Temperature dependences of D for ILs often follow the Vogel-Fulcher-Tamman (VFT) equation for diffusivity, which is described by the following equation [11,21,25] :…”
Section: Diffusion Of Neat Ionic Liquids Peg and Il/peg Mixturesmentioning
confidence: 99%
“…ILs are regarded as designer solvents due to their tunability of physical and chemical properties based on the molecular design of the cation and anion structures. 4,5 1-Ethyl-3-methyl-imidazolium acetate ([EMIM] [OAc]) is one of the most commonly used ILs for processing cellulose and chitin fibers and films, 6-8 aerogels 9,10 and for biomass pretreatment. 11 [EMIM][OAc] is used also as a medium for performing chemical reactions, in particular, for derivatisation of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12]37 Absorption of gases is another type of association that also effects the diffusivity of ions. 13 Nuclear magnetic resonance (NMR) spectroscopy is an appropriate technique for the investigation of the diffusion of ions and sorbent additives in the ILs. 14 Because of the prevalent industrial applications of ILs, they are also regarded as promising CO 2 sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…16 Also by replacing amino acid anions with N-heterocyclic anions, the viscosity of the ILs decreased significantly with improved CO 2 capture capacity. 13 In addition, it was observed that most of the amino acid based ILs become highly viscous or solidified after CO 2 absorption. However, aprotic N-heterocyclic anion (AHA) based ILs remained liquid with much faster ionic mobility after reaction with CO 2 molecules.…”
Section: Introductionmentioning
confidence: 99%